Principles of Chinese Language Teaching Based on the Material of Chinese-Ukrainian and Ukrainian-Chinese Fiction Translations - Iryna Iliychuk (Vasyl Stefanyk Precarpathian National University, 2022)
The article highlights the combination of translation and didactic areas aimed at the study and substantive application of translated artistic texts in teaching and scientific-theoretical activities, which will help to introduce elements of an innovative approach into the methodology of teaching Chinese in Ukrainian secondary and high schools and universities. Didactic materials of artistic translations from the Chinese language will introduce to pupils, students and everyone who is interested in China, its geography, history, mental traits, culture, way of living and lifestyle of the population. The problem of involving literary translations in the teaching of the Chinese language in Ukrainian linguistic didactics was not considered before. The parallel study of Chinese and Ukrainian artistic texts aims at an in-depth study of the specifics of the translation of Chinese artistic texts into Ukrainian and Ukrainian texts into Chinese. Such a linguistic and cultural approach will contribute to the further development of Ukrainian-Chinese cooperation in the humanitarian, cultural and educational spheres. The task of mastering the skill of translation appears on the agenda in foreign language education.